2019
DOI: 10.1159/000504804
|View full text |Cite
|
Sign up to set email alerts
|

Causes that Contribute to the Excess Mortality Risk in Multiple Sclerosis: A Population-Based Study

Abstract: <b><i>Background:</i></b> Lifespan is 6–10 years shorter in multiple sclerosis (MS), but the reasons remain unclear. Using linked clinical- and population-based administrative health databases, we compared cause-specific mortality in an MS cohort to the general population. <b><i>Methods:</i></b> MS patients in British Columbia (BC), Canada, were followed from the later of first MS clinic visit or January 1, 1986, to the earlier of death, emigration, or December 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 0 publications
2
20
0
Order By: Relevance
“…A total of 10 studies reported SMR for cardiovascular disease. Of these 10 studies, four were in addition to the previous publication 4,6,8,9 . The SMR for cardiovascular disease was 1.74 (95% CI 1.67 to 1.81, I 2 = 94%, p < .01).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 10 studies reported SMR for cardiovascular disease. Of these 10 studies, four were in addition to the previous publication 4,6,8,9 . The SMR for cardiovascular disease was 1.74 (95% CI 1.67 to 1.81, I 2 = 94%, p < .01).…”
Section: Resultsmentioning
confidence: 99%
“…Of these eight studies, three were new to the cohort of the previous meta-analysis. 6,8,9 The SMR for respiratory illness and infection was…”
Section: Respiratory Illness and Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…84 Cardiovascular morbidity results are similar to those reported in a recent Canadian population-based study, although CVD mortality was reported to be higher in men (n ¼ 515) compared to women (n ¼ 901) with multiple sclerosis. 85 Adults with disabilities are 4 times more likely to report their health to be fair or poor compared to people with no disabilities (40% vs 10%), 78 and women with disabilities are particularly vulnerable due to having fewer resources and protective factors. 74 Adjusted for age, women with physical disabilities have 6.6 (95% CI, 5.2-8.4) times higher odds of having CAD, 5.9 (95% CI, 4.3-8.1) times higher odds of having cardiac symptoms, 86 and are less likely to receive preventive or urgent care compared to women without disabilities.…”
Section: Disparities Beyond Sexmentioning
confidence: 99%